Efektivitas Parameter Algoritma Cheapest Insertion Heuristic (CIH) dalam Menentukan Rute Terpendek Bus Sekolah Gratis Kota Malang - Dayanti, Vivi; Jauhari, Mohammad Nafie (Jurnal Riset Mahasiswa Matematika, 2024)
This research focuses on changing parameters related to the initial value to optimize routes using the Cheapest Insertion Heuristic (CIH) algorithm, with the aim of achieving a more efficient or optimal solution. This research is a quantitative study that uses distance data between school locations from the official sources of the Department of Transportation and the Malang City government to measure the effectiveness of the CIH algorithm in determining the shortest route for school buses. This research begins by selecting two starting points using the CIH algorithm to find the optimal route. All possible pairs of starting points will be tried, then the correlation between the length of the shortest route generated and the factors considered, such as distance between the two starting points, eccentricity, betweenness centrality, eigenvector centrality, and closeness centrality, will be identified. The results showed that eigenvector centrality showed the strongest correlation with the shortest route length, with a Pearson correlation coefficient of 0,122.